Optimasi Hidrolika Sumur X Lapangan Bunyu Kalimantan Timur dengan Metode Bit Hydraulic Impact - Sri Haryono; Wira Widyawidura (Universitas Janabadra, 2016)
Bunyu Field placed on the Tarakan Basin, which is one hydrocarbon basins area of East Kalimantan. Formation that penetrated by the drill bit consist of sandstone, siltstone, clay stone and coal. Therefore, we need to rearrange the drilling mud system particularly on drilling mud hydraulics system. This study aims to optimize the hydraulic system in the process of drilling for wells X Fields Bunyu using bit hydraulic impact (BHI) method. The output of this method are to determine the optimum BHI fluid flow rate, penetrating power, nozzle size, and compare these parameters with the actual drill data before optimization (actual data) so that the penetration of the formation process is also optimal. Based on actual data of well drilling there are four (4) point penetration depth (from total 13 (thirteen) point) should be optimized particularly on drilling hydraulics system by changing the size of the aperture area on the drill nozzle in accordance with the calculation using BHI method